Strengthening of the National Hydrographic Office of Sri Lanka - A German Technical Co-operation Development Project - Bielke, U. (The International Hydrographic Review, 2015)
The project ‘Strengthening of the National Hydrographic Office of Sri Lanka’ was initiated in 1988 as a project of Technical co-operation between the Government of the Democratic Socialist Republic of Sri Lanka and the Federal Republic of Germany. Implementing agencies were the Deutsche Gesellschaft fur technische Zusammenarbeit (GTZ — German Agency for Technical Cooperation) and the National Aquatic Resources Agency of Sri Lanka (NARA). Hamburg Port Consulting, with its qualified and experienced experts in Hydrography and on account of their close co-operation with the Bundesamt fiir Seeschiffahrt und Hydrographie (BSH — Federal Maritime and Hydrographic Agency) and the Forschungsbereich Hydrographie of the Fachhochschule Hamburg (Hamburg Polytechnic — research section ‘Hydrography’), is carrying out the German part of the project by sub contract. Since 1988, experts of HPC have been working on the project in Sri Lanka. In September 1990, phase I of the Project was completed successfully. The personnel of the National Hydrographic Office (NHO) were trained in basic hydrography, an outfit of hydrographic equipment was installed and put into operation, and the NHO was enabled to produce fair-sheets. At present, phase II of the project is in progress (1990 to 1993). The objectives of phase II are the expansion and improvement of phase I to carry on the training on-the-job, to organize training courses and to install additional equipment. It is intended to procure a survey vessel and a small survey boat.